L-Theanine Content and Related Gene Expression: Novel Insights into Theanine Biosynthesis and Hydrolysis among Different Tea Plant (Camellia sinensis L.) Tissues and Cultivars - Liu, Zhi-Wei; Wu, Zhi-Jun; Li, Hui; Wang, Yong-Xin; Zhuang, Jing (Frontiers in Plant Science, 2017)
L-theanine content has tissues and cultivars specificity in tea plant (Camellia sinensis L.), the correlations of theanine metabolic related genes expression profiles with theanine contents were explored in this study. L-theanine contents in the bud & 1st leaf, 2nd leaf, 3rd leaf, old leaf, stem, and lateral root were determined by HPLC from three C. sinensis cultivars, namely ‘Huangjinya’, ‘Anjibaicha’, and ‘Yingshuang’, respectively. The theanine contents in leaves and root of ‘Huangjinya’ were the highest, followed by ‘Anjibaicha’, and ‘Yingshuang’. The theanine contents in the leaves reduced as the leaf mature gradually, and in stem were the least. Seventeen genes encoding enzymes involved in theanine metabolism were identified from GenBank and our tea transcriptome database, including CsTS1, CsTS2, CsGS1, CsGS2, CsGOGAT-Fe, CsGOGAT-NAD(P)H, CsGDH1, CsGDH2, CsALT, CsSAMDC, CsADC, CsCuAO, CsPAO, CsNiR, CsNR, CsGGT1, and CsGGT3. The transcript profiles of those seventeen genes in the different tissues of three tea plant cultivars were analyzed comparatively. Among the different cultivars, the transcript levels of most selected genes in ‘Huangjinya’ were significantly higher than that in the ‘Anjibaicha’ and ‘Yingshuang’. Among the different tissues, the transcript levels of CsTS2, CsGS1, and CsGDH2 almost showed positive correlation with the theanine contents, while the other genes showed negative correlation with the theanine contents in most cases. The theanine contents showed correlations with related genes expression levels among cultivars and tissues of tea plant, and were determined by the integrated effect of the metabolic related genes.